Bringing up Baby [videorecording (DVD)] - Hepburn, Katharine, 1907-2003; Ruggles, Charlie, 1886-1970; Grant, Cary, 1904-1986; Catlett, Walter, 1889-1960; Fitzgerald, Barry, 1888-1961; Wilde, Hagar (Criterion collection ;, 2021)
"Screwball sparks fly when Cary Grant and Katherine Hepburn let loose in one of the fastest and funniest films ever made--a high-wire act of invention that took American screen comedy to new heights of absurdity. Hoping to procure a million-dollar investment from a wealthy society matron for his museum, a hapless paleontologist (Grant) finds himself entangled with a dizzy heiress (Hepburn) as the manic misadventures pile up--a missing dinosaur bone, a leopard on the loose, and plenty of gender-bending mayhem among them. Bringing Up Baby's sophisticated dialogue, spontaneous performances, and giddy innuendo come together in a whirlwind of comic chaos captured with lightning-in-a-bottle brio by director Howard Hawks"--Container.